A comparative Study of use of Preparation Containing Ferrous sulphate versus Ferrous fumarate in Treatment of Iron Deficiency Anemia - Arora Bhoomi, D (International Journal of Pharmaceutical & Biological Archive, 2011)
Objective: The present study was undertaken with the aim of determining and comparing the efficacy of ferrous sulphate and ferrous fumarate in increasing haemoglobin level in girls in the age range of 12 to 17 years suffering from iron deficiency anemia.Study design: A total number of 100 adolescent girls of lower socio economic class studying in Government Secondary School, Anand, who were diagnosed as suffering from anemia were selected and randomly divided into 2 groups. One group was given ferrous sulphate and the other group was given ferrous fumarate for one month.Changes in body weight, haemoglobin level, RBC count and MCV value were estimated twice-first after 10 days and then at the end of one month.The data so recorded was than analyzed by chi-square test and Paired sample T- test to compare the efficacy of the two iron preparations in study groups.Results: Observations revealed that increase in body weight was found to be more with the use of ferrous fumarate than with ferrous sulphate while increase in haemoglobin level, RBC count and MCV value was found to be more with use of ferrous sulphate than with ferrous fumarate.Conclusion: Ferrous sulphate is found to be more effective in increasing haemoglobin levels and RBC counts as compared to ferrous fumarate in adolescent girls suffering from iron deficiency anemia.